Faktor Penyebab Kesulitan Siswa Dalam Pelaksanaan Pembelajaran Daring: Survei di SDN 2 Mapin Kebak - Nopitasari Nopitasari; Nasaruddin Nasaruddin; Heri Setiawan; I Nyoman Karma (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
This study aims to determine the level of factors that cause student difficulties in implementing online learning at SDN 2 Mapin Kebak in the 2020/2021 school year. The subjects in this study were classes II, III, IV and V, totaling 89 students, while the object was the students' difficulties in online learning. The data collection technique uses a questionnaire with a survey method. The data analysis technique used is descriptive quantitative with percentages. The results of the study generally show the level of factors that cause student difficulties in implementing online learning at SDN 2 Mapin Kebak for the 2020/2021 school year in the